Adding metoclopramide to paroxetine induced extrapyramidal symptoms and hyperprolactinemia in a depressed woman: a case report - Igata R; Hori H; Atake K; Katsuki A; Nakamura J (Neuropsychiatric Disease and Treatment)
Ryohei Igata, Hikaru Hori, Kiyokazu Atake, Asuka Katsuki, Jun Nakamura Department of Psychiatry, University of Occupational and Environmental Health, Kitakyushu, Japan Abstract: A 54-year-old Japanese woman was diagnosed with major depressive disorder and prescribed paroxetine 20 mg/day. In around May 2013, the patient experienced gastric discomfort, so metoclopramide was prescribed. Beginning on June 4, 2013, the patient was given metoclopramide, 10 mg intravenously, twice per week. On the seventh day after beginning metoclopramide, facial hot flushes, increased sweating, muscle rigidity, and galactorrhea were noted. Extrapyramidal symptoms (EPS) rapidly subsided in response to an intramuscular injection of biperiden. Blood biochemical tests revealed an elevated serum prolactin level of 44 ng/mL. After stopping metoclopramide, EPS disappeared. Serum prolactin level decreased to 15 ng/mL after 4 weeks. In our case, although no adverse reactions had previously occurred following the administration of metoclopramide, the patient developed EPS and hyperprolactinemia following the administration of this antiemetic in combination with paroxetine. Paroxetine and metoclopramide are mainly metabolized by CYP2D6, and they are inhibitors for CYP2D6. We report a case with EPS and hyperprolactinemia whose plasma paroxetine and metoclopramide level rapidly increased after the addition of metoclopramide. Our experience warrants the issuing of a precaution that adverse reactions may arise following the coadministration of metoclopramide and paroxetine even at their respective standard dose levels. Keywords: metoclopramide, paroxetine, extrapyramidal symptoms, SSRI, hyperprolactinemia, depression